Self-esteem, empathy and their impacts on cyberbullying among young adults - Balakrishnan, Vimala; Fernandez, Terence (Elsevier, 2018)
This paper investigated the impacts of self-esteem and empathy on cyber bullies, victims and bystanders. Additionally, it also examined their impacts on emotional responses experienced, and actions taken by the perpetrators, victims and bystanders. Self-administered surveys were used to gather data from a large sample of 1263 young adults, mostly university students in Malaysia (Mage = 20.9 years; SD = 1.22). The Rosenberg Self-Esteem Scale and Toronto Empathy Scale were used to measure self-esteem and empathy, respectively. Binary logistic regressions revealed no significant impacts of self-esteem and empathy on the participants, regardless of their roles. However, self-esteem was found to have significant relationships with victims’ feeling angry and reporting a cyberbullying incident. As for bystanders, self-esteem also had significant relationships with feeling angry, sad, victim-pity and defending the victims. Empathy had no significant relationships with any of the actions and emotional responses for bullies, victims and bystanders.